Occurrence of enteric viruses causing clinical diarrhea in small ruminants in northern Indian plains: a reverse transcription PCR based molecular study - Sapna Prajapati; Kumaresan, Gururaj; Manish Kumar; Dimple Andani; Anil Kumar Mishra; Ashok Kumar; R.V.S. Pawaiya; Nitika Sharma; Anu Rahal; Dinesh Kumar Sharma (Veterinaria Italiana, 2023)
Fowlpox virus (FPV) infects chickens and turkeys giving rise to pock lesions on various body parts like combs, wattles, legs, shanks, eyes, mouth, etc. The birds, affected with FPV, also show anemia and a ruffled appearance which are clinical symptoms of reticuloendotheliosis. Interestingly, the field strains of FPV are integrated with the provirus of reticuloendotheliosis virus (REV). Due to this integration, the infected birds, upon replication of FPV, give rise to free REV virions, causing severe immunosuppression and anemia. Pox scabs, collected from the infected birds, not only show positive PCR results upon performing FPV-specific 4b core protein gene PCR but also show positive results for the PCR of REV-specific env gene and FPV-REV 5’LTR junction. Homogenized suspension of the pock lesions, upon inoculating to the chorio-allantoic membrane (CAM) of 10-day-old specific pathogen-free embryonated chicken eggs, produces characteristic pock lesions in serial passages. However, the lesions also harbor REV mRNA or free virion, which can be identified by performing REV-specific env gene PCR using REV RNA from FPV-infected CAMs. The study suggests successful replication and availability of REV mRNA and free virion alongside the FPV, although the CAM is an ill-suited medium for any retroviral (like REV) growth and replication.